2001
DOI: 10.1034/j.1600-0676.2001.021004254.x
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of hepatitis B surface antigen in chronic carriers of hepatitis delta antibodies

Abstract: HBsAg clearance is increased over the years in HDV patients compared to ordinary HBsAg carriers, and is often associated with improvement of HDV disease without seroconversion to anti-HBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 17 publications
2
16
2
2
Order By: Relevance
“…In agreement with a previous report (17), at the two time-points evaluated in the present investigation viremia levels of the two viruses fluctuated widely, an observation that could be related to either intrinsic mechanisms of reciprocal HDV-HBV inhibition or to the variable progression of the underlying liver disease (21). Seroclearance of HBsAg in patients with HDV chronic infection represents the ultimate step in the process of HDV clearance (22). Indeed, as long as the HBsAg is produced, HDV can thrive and sustain replication and liver disease.…”
Section: Discussionsupporting
confidence: 80%
“…In agreement with a previous report (17), at the two time-points evaluated in the present investigation viremia levels of the two viruses fluctuated widely, an observation that could be related to either intrinsic mechanisms of reciprocal HDV-HBV inhibition or to the variable progression of the underlying liver disease (21). Seroclearance of HBsAg in patients with HDV chronic infection represents the ultimate step in the process of HDV clearance (22). Indeed, as long as the HBsAg is produced, HDV can thrive and sustain replication and liver disease.…”
Section: Discussionsupporting
confidence: 80%
“…15 Consistent with the superior results achieved in therapy of chronic HBV and HCV diseases using pegylated rather than standard IFN, the results of our study would also support the use of PEG-IFN as a first-line therapy and the recommendation to initiate therapy as early as possible for those with chronic hepatitis D. In fact, the efficacy of standard IFN-␣ in the treatment of chronic delta hepatitis (CHD) remains controversial; the few controlled and the many small uncontrolled trials of the use of standard IFN as a treatment for CHD found that HDV synthesis was suppressed in a fraction of patients while on therapy, but treatment failed to induce sustained clearance of the virus post-therapy; transient and occasionally even permanent clearance of HDV can also occur spontaneously in untreated patients. 26 At variance with the delayed clearance of HBsAg after spontaneous or standard IFN-induced clearance of HDV RNA from serum, [21][22][23][24][25][26][27] in the present study none of the patients treated with PEG-IFN who achieved a sustained response cleared this antigen, possibly because of the relatively short posttreatment follow-up.…”
Section: Discussionmentioning
confidence: 51%
“…Nevertheless clinical manifestations of liver disorders range from an asymptomatic carrier state to fulminant hepatitis and cirrhosis [10]. Disease resolution can occur in the natural history of HDV infection, leading to HBsAg seroclearance [11], and an historical benign course has been described in the Greek island of Rhodes and in American Samoa. In general, patients with hepatitis delta have a progressive disease, evolving to a stable or decompensated cirrhosis.…”
Section: Pathogenesismentioning
confidence: 99%